A note on simplicity of contact Lie algebras over GF(2) - Zargeh, C. (Algebra and Discrete Mathematics, 2017)
In this note we investigate the structure of contact Lie algebras when the ground field is of characteristic 2. In order to describe the simple constituent of contact Lie algebras, by using computer algebra system, GAP, we make a conjecture which says that the quotient algebra of contact Lie algebra by its Nilradical is simple and there exits an isomorphism among this constituents and Witt Lie algebras and Hamilton Lie algebras.